The Effect of Disaster Management Preparedness and Risk Perception on Community Psychological Resilience with Stress Coping as a Mediating Variable - Muksalmina Muksalmina; Ahmad Syahyana; Ferdy Hidayatullah; Tibyan Asyukri; Novita Novita; Edi Saputra Ringga (Heca Sentra Analitika, 2025)
Communities living in disaster-prone areas need not only structural preparedness but also a strong psychological capacity to survive and recover from disaster threats. This study examines the influence of Disaster Management Preparedness and Risk Perception on Community Psychological Resilience, with Stress Management as a mediating variable. Using a quantitative associative approach, data were collected from residents of disaster-prone areas in Banda Aceh City and Aceh Besar Regency, Indonesia, through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that disaster management preparedness and risk perception significantly influence stress management and psychological resilience. Stress management emerged as the strongest predictor of resilience and served as a significant mediator in the relationship between preparedness and resilience, as well as between risk perception and resilience. These results highlight that resilience is strengthened not only by knowledge and structural preparedness, but also by adaptive coping strategies such as problem-focused coping, emotion regulation, and religion-based coping. In the context of Aceh Province, where socio-cultural and religious values strongly shape individual responses to disaster threats, coping mechanisms act as important psychological pathways that transform preparedness and risk awareness into resilient behavior. This study provides practical implications for disaster management authorities to integrate psychosocial strengthening into preparedness programs, emphasizing community education, simulation activities, and culturally rooted psychosocial support to enhance community resilience. Further research is encouraged to adopt mixed methods and explore additional socio-cultural variables to deepen the understanding of resilience dynamics in disaster-prone communities.